Potential of Fermentation in Detoxifying Toxic Cassava Root Tubers - Andama, Morgan; Lejju, Julius Bunny (Journal of Agricultural Science and Technology, 2012)
Quantitative determination of hydrogen cyanide (HCN) content in a toxic local cassava variety “Rutuga” with an initial total HCN of 16.65%, free HCN of 9.19% and bound HCN (cyanoglycosides) of 7.46% in the fresh peeled root tubers was done to assess the effectiveness of aquatic and terrestrial (heap) fermentation in detoxifying cassava root tubers for obtaining dried product used in making flour. This was indirectly done by getting the difference in HCN content that remained after processing the root tubers using some traditional processing techniques. The findings indicated that aquatic fermentation in water from river Rwizi for 4 days only removed 1.23% of total HCN, 0.05% of free HCN and 2.68% of Cyanoglycosides (bound HCN) while terrestrial (heap) fermentation for 4 days removed 50.33% of total HCN, 20.84% of free HCN and 86.66% of Cyanoglycosides (bound HCN). Therefore, terrestrial (heap) fermentation has a higher potential in removing total HCN, free HCN and cyanoglycosides (bound HCN) than aquatic fermentation, especially in water from river Rwizi.
Keywords: Aquatic fermentation; Cassava; Hydrogen cyanide; Terrestrial fermentation